Assessment of genetic diversity in a collection of Ghanaian okra germplasm (abelmoschus spp l.) using morphological markers. - Oppong-Sekyere, Daniel (2011)
A thesis submitted in partial fulfillment of the requirements for the award of a Master of Science degree in Crop Science, Agronomy (Plant Breeding) at the Kwame Nkrumah University of Science and Technology, Kumasi, Ghana.